2021
DOI: 10.1371/journal.pone.0254023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of NiMoO4/nanographite nanocomposite electrodes using flexible graphite substrate for aqueous hybrid supercapacitors

Abstract: The cycling performance of supercapacitors sometimes becomes limited when electrode materials slough off during frequent charge–discharge cycles, due to weak bonding between the active material and the current collector. In this work, a flexible graphite foil substrate was successfully used as the current collector for supercapacitor electrodes. Graphite foil substrates were treated in different ways with different acid concentrations and temperatures before being coated with an active material (NiMoO4/nanogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…5(f) from which reveals the has highest specific capacitance for the sample x = 0.06, and the same were tabulated in Table 3. From the table, it was also observed that the specific capacitance decreases with an increase in scan rate because faster redox reactions take place at a higher scan rate, reducing electrolyte ion diffusion into the material and consequently lowering the capacitance [35]. Using the GCD test, the specific capacitance (Csp), energy density (Ed), and power density (Pd) were calculated by adopting the expressions [36].…”
Section: Resultsmentioning
confidence: 99%
“…5(f) from which reveals the has highest specific capacitance for the sample x = 0.06, and the same were tabulated in Table 3. From the table, it was also observed that the specific capacitance decreases with an increase in scan rate because faster redox reactions take place at a higher scan rate, reducing electrolyte ion diffusion into the material and consequently lowering the capacitance [35]. Using the GCD test, the specific capacitance (Csp), energy density (Ed), and power density (Pd) were calculated by adopting the expressions [36].…”
Section: Resultsmentioning
confidence: 99%
“…Such decrease is related to diffusion limitations of electrolyte in pores of electrode material. 33,67,68 However, 83% of the areal capacitance calculated from the CV obtained at the scan rate of 5 mV s À1 was preserved at the scan rate of 100 mV s À1 , indicating a good high-rate capability of the CCSCs (Fig. 3E).…”
Section: Electrochemical Characterization Of CC Electrodes and Ccscsmentioning
confidence: 97%
“…This is so because this strategy offers the most convenient processes and yet conducive outcomes. Table 6 is to impart a brief account of a host of developments in catalytic properties of NiMoO 4 done involving heterostructures and hybrids 121,123,256‐382 . in many cases, doping, defect and/or morphology engineering have been amalgamated with the heterostructure for superior enhancement in catalytic properties either to generate more surface area or more population of active sites or for other special necessities as summarized in Table 6.…”
Section: Tuning the Properties Of Nimoo4 By Different Approachesmentioning
confidence: 99%
“…Table 10 is to summarizes a few notable works pertaining to improvement in supercapacitor performance by employing NiMoO 4carbon-based composites. 202,226,256,259,266,270,277,280,285,287,290,297,310,316,320,326,330,337,344,347,348,[350][351][352]356,363,372,374,380,381,390…”
Section: Nimoo 4 -Carbon Based Compositesmentioning
confidence: 99%
See 1 more Smart Citation